Aumento da suscetibilidade ao pentilenotetrazol após a sobrevivência de um quadro de malária cerebral em camundongos - Grauncke, Ana Claudia Beck (2017)
Malaria is considered a neglected disease and public health problem, affecting more than 200 million people worldwide. Plasmodium falciparum, one of the four human parasitic species, is responsible for the development of severe malaria, which can lead to coma or patient death. One of major manifestation of this infection is cerebral malaria (CM), a neurological complication and a potential cause of epilepsy in malaria-endemic regions. In the present study we used the Plasmodium berghei ANKA (PbA) model of experimental cerebral malaria (CM) in C57BL/6 male mice (CEUA 020, 2014), where was verified the susceptibility of pentylenetetrazol (PTZ) - induced seizures 45 days after infection, with rescue from CM and parasite clearance, through electroencephalographic analysis. Our results showed that the administration of a subconvulsant dose of pentylenetetrazol (30 mg/Kg) is capable to alter the latency to myoclonic and tonic-clonic seizures in infected mice, as well increase the duration of tonic-clonic seizures. In addition, quantitative analysis of electroencephalogram revealed a decrease in relative power at beta frequency band in PbA-infected animals after PTZ injection. EEG recordings demonstrated an increased susceptibility of mice infected with PbA to myoclonic, tonic-clonic seizures. These results demonstrated that experimental cerebral malaria caused central nervous system (CNS) changes that facilitate the occurrence and increase the duration of seizures. However, additional studies are necessary to evaluate the molecular mechanisms underlying our findings as well as its clinical implications.